Simulation Assisted Nanoscale Imaging of Single Live Cells with Scanning Electrochemical Microscopy. Issue 2 (25th October 2018) - Filice, Fraser P.; Li, Michelle S. M.; Ding, Zhifeng
Abstract: Nanoelectrodes have become an area of significant interest in recent years, which provide a number of advantages for imaging with scanning electrochemical microscopy (SECM). Since the resolution of SECM imaging is directly dependent on the size of the electrode probe, the reduced surface area of nanoelectrodes allows for the imaging of smaller sample features, or more localized electrochemical reactivity. Nanoelectrodes with a radius of 130 nm are employed to image the surface of single live cells. The use of nanoscale imaging, however, introduces additional complexity into the simulation modeling of the cell surface geometry and electrochemical reactivity. The creation of tailored simulation models accounting for these specific physical conditions is utilized to overcome the additional challenges to the characterization of the electrochemical system. Methodologies for the experimental mapping and creation of 3D simulation models of single live cells have been well developed, which are presented herein. These developments include characterization of cell surface topography, tip‐to‐cell distance, as well as cell membrane permeability quantification. The advanced quantification of the complex nanoscale imaging of single live cells assisted by theoretical simulations provides increased versatility to SECM as an already powerful bioanalytical tool. Abstract : Nanoscale imaging of single live cells by scanning electrochemical microscopy (SECM) as well as 3D simulation modeling are conducted successfully. Characterization of cell surface topography, tip‐to‐cell distance, and cell membrane permeability quantification are simple and straightforward. This work provides increased versatility to SECM as an already powerful bioanalytical tool.